2009
DOI: 10.1007/s11207-009-9345-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Weak Polar Fields of Solar Cycle 23: Investigation Using OMNI for the STEREO Mission Period

Abstract: The current solar cycle minimum seems to have unusual properties that appear to be related to weak solar polar magnetic fields. We investigate signatures of this unusual polar STEREO field in the ecliptic near-Earth interplanetary magnetic field (IMF) for the STEREO period of observations. Using 1 AU OMNI data, we find that for the current solar cycle declining phase to minimum period the peak of the distribution for the values of the ecliptic IMF magnitude is lower compared to a similar phase of the previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
50
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 24 publications
7
50
0
Order By: Relevance
“…It is well known that the late declining phase of solar cycle 23 and the following minimum were unusually long and deep when compared to three previous corresponding phases (e.g., Russell et al, 2010;Jian et al, 2011). The global solar magnetic field had significant differences between our study periods that were reflected throughout the heliosphere (e.g., Lee et al, 2009;Cremades et al, 2011;Jian et al, 2011) and as we will show, affected the solar wind structure surrounding magnetic clouds. The minimum following cycle 22 was a "typical" solar minimum featuring a dipole-like solar magnetic field and large polar coronal holes, while during the recent minimum, the global magnetic field of the Sun had a multipole structure, and as a consequence, low-and mid-latitude coronal holes were frequently present (Abramenko et al, 2010).…”
Section: Introductionmentioning
confidence: 42%
See 1 more Smart Citation
“…It is well known that the late declining phase of solar cycle 23 and the following minimum were unusually long and deep when compared to three previous corresponding phases (e.g., Russell et al, 2010;Jian et al, 2011). The global solar magnetic field had significant differences between our study periods that were reflected throughout the heliosphere (e.g., Lee et al, 2009;Cremades et al, 2011;Jian et al, 2011) and as we will show, affected the solar wind structure surrounding magnetic clouds. The minimum following cycle 22 was a "typical" solar minimum featuring a dipole-like solar magnetic field and large polar coronal holes, while during the recent minimum, the global magnetic field of the Sun had a multipole structure, and as a consequence, low-and mid-latitude coronal holes were frequently present (Abramenko et al, 2010).…”
Section: Introductionmentioning
confidence: 42%
“…Our analysis shows that the low number of magnetic storms during Period 2 was attributed to the lack of both CME and non-CME associated storms. Several studies have shown that during the recent low solar activity period the near-ecliptic IMF and dynamic pressure were about 30 % weaker (e.g., Lee et al, 2009;Jian et al, 2011), CMEs were slower (Vourlidas et al, 2011) and ICMEs Kilpua et al, 2012;Jian et al, 2011) had weaker magnetic fields and lower speeds than reported during the previous solar minimum. This generally weaker IMF and dynamic pressure in stream interaction regions and in ICMEs presumably led to weaker geomagnetic consequences.…”
Section: Discussionmentioning
confidence: 95%
“…The consequences of these weaker solar magnetic fields were visible in changes of the solar wind plasma flow through the interplanetary medium. Observations near the Earth orbit during the end-phase of solar cycle 23 demonstrated that the IMF strength and solar wind density were about 30 % lower than in the minimum 22/23, and the momentum flux was about 38 % lower , whereas the solar wind speed remained unchanged compared with the previous solar minimum (Lee et al, 2009). At the same time, the Ulysses (Balogh et al, 1992;Bame et al, 1992) out-of-ecliptic observations show comparable changes throughout the heliosphere, namely a reduction in the radial magnetic field by about 64 %, of the dynamic pressure by about 22 %, and of the thermal pressure by about 25 % (Smith and Balogh, 2008;McComas et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…As discussed in Sect. 1 also coronal and heliospheric magnetic fields were significantly lower during the SC 23 minimum than during a few previous solar cycles (Wang et al, 2009;Lee et al, 2009). In addition, the warped and high-latitude streamer belt configuration observed during the SC 23 minimum (Sect.…”
Section: Discussion and Summarymentioning
confidence: 73%
“…This extended period of low solar activity and uncommon solar magnetic field configuration produced interesting consequences throughout the heliosphere. Lee et al (2009) investigated the effects of the weak polar fields in the ecliptic near-Earth interplanetary medium and they found that the interplanetary magnetic field (IMF), density and momentum flux were lower by 30 %, 30 % and 38 %, respectively, compared to a similar phase of the SC 22 minimum.…”
Section: Introductionmentioning
confidence: 99%